2001
DOI: 10.1152/physiolgenomics.00078.2001
|View full text |Cite
|
Sign up to set email alerts
|

Optical dysfunction of the crystalline lens in aquaporin-0-deficient mice

Abstract: Aquaporin-0 (AQP0), a water transport channel protein, is the major intrinsic protein (MIP) of lens fiber cell plasma membranes. Mice deficient in the gene for AQP0 (Aqp0, Mip) were generated from a library of gene trap embryo stem cells. Sequence analysis showed that the gene trap vector had inserted into the first exon of Aqp0, causing a null mutation as verified by RNA blotting and immunochemistry. At 3 wk of age (postnatal day 21), lenses from null mice (Aqp0(-/-)) contained polymorphic opacities, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
137
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(145 citation statements)
references
References 32 publications
8
137
0
Order By: Relevance
“…However, three natural AQP0 mutations in human (Berry et al, 2000;Francis et al, 2000a,b;Geyer et al, 2006), and three in mice (Cataract Fraser, Cat Fr : Shields and Griffin, 1993;Shiels et al, 2000; Cataract lens opacity, Cat lop : Shiels and Bassnett, 1996;Cataract Tohoku, Cat Tohm : Okamura et al, 2003) have been associated with autosomal dominant cataracts. Moreover, targeted inactivation of AQP0 in mice resulted in cataract (Shiels et al, 2001). These data on humans and mice illustrate the importance of AQP0 for lens transparency and homeostasis.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, three natural AQP0 mutations in human (Berry et al, 2000;Francis et al, 2000a,b;Geyer et al, 2006), and three in mice (Cataract Fraser, Cat Fr : Shields and Griffin, 1993;Shiels et al, 2000; Cataract lens opacity, Cat lop : Shiels and Bassnett, 1996;Cataract Tohoku, Cat Tohm : Okamura et al, 2003) have been associated with autosomal dominant cataracts. Moreover, targeted inactivation of AQP0 in mice resulted in cataract (Shiels et al, 2001). These data on humans and mice illustrate the importance of AQP0 for lens transparency and homeostasis.…”
Section: Introductionmentioning
confidence: 67%
“…Studies on AQP0 knockout mouse lens showed an 80% reduction in the fiber cell membrane water permeability compared to the wild type lens (Shiels et al, 2001). Several research groups have investigated the expression, localization (Patil et al, 1997;Hamann et al, 1998;Zampighi et al, 2003;Varadaraj et al, 2005), and interaction of this protein with other lens proteins (Zampighi et al, 2002;Tan et al, 2004;Yu and Jiang, 2004;Fan et al, 2005;Yu et al, 2005;Rose et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in AQP0 are associated with hereditary cataracts in mice and humans Shiels et al, 2001). Cataract-producing AQP0 mutations are thought to produce endoplasmic reticulum-retained and non-functional AQP0 Geyer et al, 2006); however, the mechanism linking AQP0 loss-of-function and cataracts remains unclear.…”
Section: Aqp0 Mutations Cause Congenital Cataractsmentioning
confidence: 99%
“…Cataract-producing AQP0 mutations are thought to produce endoplasmic reticulum-retained and non-functional AQP0 Geyer et al, 2006); however, the mechanism linking AQP0 loss-of-function and cataracts remains unclear. Proposed mechanisms include loss of AQP0-facilitated fiber-fiber adherence (Shiels et al, 2001), and impaired fiber cell dehydration (Fotiadis et al, 2000).…”
Section: Aqp0 Mutations Cause Congenital Cataractsmentioning
confidence: 99%
“…On protein reconstitution, arrays of junctional octamers, proposed to link two cells together, have also been observed (12). Loss of AQP0 leads to disorganized fiber cells and lens opacity (18,43,44), raising the question of whether this protein serves primarily as a water channel that functions in water homeostasis and microcirculation of nutrients and waste products (45), or as a cell-adhesion molecule (12,(14)(15)(16) that promotes the optically critical close apposition of fiber cells, or both. A related question is the functional significance of the low permeability of AQP0 relative to other aquaporins.…”
Section: Biological Relevance Of Slow Transport By Aqp0 and Implicatimentioning
confidence: 99%